1968
DOI: 10.1111/j.1365-3180.1968.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phytotoxicity of Some Herbicides in Field and Pot Experiments in Relation to Soil Properties

Abstract: Summary. The phytotoxicities in a number of soils of lenacil, linuron, prometryne and simazine to two indicator plants were determined in field and glasshouse experiments. The results were compared with estimates of the adsorption capacity of the soils obtained by two methods using dimethylaminobenzaldehyde as a model adsorbate. The possible influence of other soil properties was also considered. One of the adsorption measurements had some predictive value for glasshouse behaviour but was not markedly superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1970
1970
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…An important factor affecting availability and subsequent phytotoxicity of herbi cides is adsorption onto soil colloids (7,13,18,19,20,22). Although phenylurea herbicide adsorption has been demon strated in pure silicate clay systems (2, 6), there is strong correlative evidence that the organic fraction of the soil is of primary importance in adsorption (5,10,11,12,14,15,19).…”
Section: Introductionmentioning
confidence: 99%
“…An important factor affecting availability and subsequent phytotoxicity of herbi cides is adsorption onto soil colloids (7,13,18,19,20,22). Although phenylurea herbicide adsorption has been demon strated in pure silicate clay systems (2, 6), there is strong correlative evidence that the organic fraction of the soil is of primary importance in adsorption (5,10,11,12,14,15,19).…”
Section: Introductionmentioning
confidence: 99%
“…whereas climatic factors were of only minor significance. However, Hance et al (1968) found that soil organic matter was significantly correlated with 3 -793832 siniazine phytotoxicity in greenhouse experiments but provided a poor estimate of phytotoxicity in field trials, where climatic factors seemed to be more important than soil type. Under Danish conditions Petersen (1970) found a negative relation bet\vecn the leachability of simazine and soil organic matter content.…”
Section: Introductionmentioning
confidence: 91%
“…The specimen tubes were weighed periodically and when they had lost I g water, 1 ml was pipetted onto the surface. The plants from duplicate pots were harvested after 4,7,9,11,14,16,18 and 21 days and the amounts of herbicide accumulated were determined as previously described. The contents of six specimen tubes were transferred to centrifuge tubes at intervals during the experimental period.…”
Section: Uptake By Plantsmentioning
confidence: 99%